Purwarupa Sistem Monitoring Kemiringan Menara Base Transceiver Station (BTS) Berbasis Arduino sebagai Solusi Maintenance Menara - Sam Benyamin; Nachrowie Nachrowie; Wahyu Dirgantara (JASIEK (Jurnal Aplikasi Sains, Informasi, Elektronika dan Komputer), 2022)
Menara Base Transceiver Station (BTS) is a telecommunications station whose main function is to facilitate wireless communication between communication devices (clients) and network operators. BTS towers are usually built in densely populated residential areas, due to distributing telecommunications networks. Because it was built in a densely populated settlement, it is necessary to pay attention to the feasibility maintenance of the BTS tower. BTS tower maintenance is intended so that BTS towers can work optimally and reduce the risk of collapsing. The prototype will be made with several components, namely the MPU-6050 sensor, Arduino Uno and LCD. MPU-6050 to detect the tilt of the BTS tower. After 10 tests of pitch and roll angles, the prototype of the BTS tilt has an average error of 1.077 for pitch angle and 1.703 for roll angle. These results are still valid in monitoring the angle of inclination of the BTS